Operating conditions of an active beamer and its effect on the performance - Shah Rachit (2016)
Active Beamers (ABM) are becoming increasingly popular in today’s world over the conventional ACMV systems due to their energy saving potential and the reduced operating costs. This dissertation aims to explore the first ever reported ABM model and conduct various simulations to validate the model. It presents a comparison study of the performance as well as the operating region under different operating conditions. Two cases have been considered: 1) measurement with sensor uncertainty 2) measurement with sensor uncertainty. The chilled water inlet temperature must be maintained above the space dew point temperature to avoid condensation. The operating conditions of ABM under which it can be operated efficiently without any condensation are checked by using this model. For this, different margins of safety are added to the dew point temperature. Performance indicators for different cases are also simulated by varying chilled water volume flow rates and primary air plenum pressures to know the effectiveness of model under different operating conditions. A comparison is also done between the two cases and the effect of sensor uncertainty errors on the operating region is shown. Based on the simulation results and observations, guidelines are given to operate the ABM efficiently with lower energy consumption and running costs. The model can be checked under various operating conditions to gain a better insight on the operation of the ABM.